Caries experience in relation to salivary physicochemical and immunological changes among asthmatic patients in Mosul city / Iraq - Mohammed S Younus; Ahlam T Mohammed (College of Dentistry/ University of Baghdad, 2013)
Background: Asthma is a pulmonary disorder characterized by reversible stenosis of the peripheral bronchi. This disease could affect the oral health; as a result asthmatic patients may have a higher risk of developing dental diseases. This study was conducted to evaluate the caries experience and salivary elements among asthmatic patients using Ventoline inhaler. Materials and methods: The study group consisted of 30 male asthmatic patients with an age range 20-24years (under Ventoline inhaler). The control group includes 30 subjects matching with study group in age and gender. Plaque and DMFS index were used for recording caries experience. Stimulated salivary samples were collected and then salivary flow rate, S-IgA and salivary elements concentrations (Ca, Na, K and PO4) were determined. Results: The mean value of dental caries (DMFS) and plaque index (Pl I) were found to be higher among study group compared to control group with statistically significant difference for Pl I (P0.05). The mean value of salivary flow rate, Ca, PO4 , Na and K ions concentrations were found to be lower among study group compared to the control group with no statistically significant difference (P>0.05), except for Ca and K ions the differences were statistically significant (P0.05). Conclusions: Individuals with asthma have a higher caries prevalence, worse oral cleanliness and lower salivary elements compared to the control group, so a special preventive programs need to be designed for those patients.